Otoacoustic emission testing in Ghanaian children with sickle‐cell disease. Issue 9 (21st May 2015) - Kegele, Josua; Hurth, Helene; Lackner, Peter; Enimil, Anthony; Sylverkin, Justice; Ansong, Daniel; Nkyi, Clara; Bonsu, Benedicta; Agbenyega, Tsiri; Schartinger, Volker H.; Schmutzhard, Erich; Zorowka, Patrick; et al.
Abstract Objective To evaluate hearing loss in children as a complication of sickle‐cell disease. Methods In Kumasi, Ghana, 35 children with SCD aged 6 months to 10 years underwent transient‐evoked otoacoustic emissions testing (TEOAE) to investigate the function of the inner ear. Healthy Ghanaian children recruited in school and kindergarten served as controls. Results One of 35 children with SCD and 13 of 115 control children failed the otoacoustic emissions testing. This difference between the control group and the children with SCD was not statistically significant. Conclusion Early hearing impairment does not regularly occur in sickle‐cell disease, and in children, it is not a likely cause of delayed or impaired language development.